1999
DOI: 10.1046/j.1524-4725.1999.98246.x
|View full text |Cite
|
Sign up to set email alerts
|

The Histologic Evaluation of Pulsed Carbon Dioxide Laser Resurfacing versus Phenol Chemical Peels in Vivo

Abstract: With the parameters used in this study, phenol peels resulted in the formation of a thicker zone of collagen despite the deeper ablation depth of the laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
3
18
1
1
Order By: Relevance
“…Protein coagulation is observed in the epidermis immediately after application of 88% phenol solution 55 . It can penetrate deep in to the tissue, down to upper reticular dermis 56 . All phenol compounds have toxicity towards melanocytes.…”
Section: % Phenol Solutionmentioning
confidence: 99%
“…Protein coagulation is observed in the epidermis immediately after application of 88% phenol solution 55 . It can penetrate deep in to the tissue, down to upper reticular dermis 56 . All phenol compounds have toxicity towards melanocytes.…”
Section: % Phenol Solutionmentioning
confidence: 99%
“…Knochenabbaus eine systemische Dauersubstitution erforderlich [33].Es gibt Hinweise, dass chemische Peelings (Glycolsäure, Fruchtsäure, Trichloressigsäure, Phenol) die Kollagensynthese und die Hyaluronsäurekonzentration in der Dermis erhöhen [6,40]. Dermabrasion und Laserabrasion sind mechanische Verfahren, die das Hautrelief eher vorüberge-hend verbessern.…”
Section: Der Hautarzt 9 · 2003 826unclassified
“…It is reported that, compared to laser resurfacing, phenol peeling forms thicker new collagen after treatment although initial skin destruction is less. This suggests it is more effective in lifting wrinkles 5 . Wu et al.…”
Section: Discussionmentioning
confidence: 97%